Nickel Supported Natural Zeolite as a Bifunctional Catalysts for Conversion of Citronella Oil Crude to Menthols - Ralentri Pertiwi; Silvester Tursiloadi; Indri Badria Adilina; Kiky Corneliasari Sembiring; Yuya Oaki (Research Center for Chemistry - LIPI, 2016)
Characterization and catalytic activity of modified natural zeolite for the conversion of citronella oil to menthol was investigated. In this research, natural zeolite was prepared by acid activation with HCl and impregnated with Ni metal. The addition of Ni metal of around 12.5 nm in diameter provided a bifunctional catalyst for two steps of citronella oil conversion i.e. cyclization and hydrogenation. The process was performed in a one-pot reaction system by stirring at 200oC with pressure of 20 bar H2 for 3h. The reaction products changed slightly with varieties of reaction temperature and amount of catalysts employed. Results showed that Ni/NZB-HT catalyst was the best catalyst which was able to convert citronella oil to menthol with a selectivity of 50% menthol and 100% conversion of citronellal.